Classical Dance-Metaheuristic: A Metaheuristic Optimization Algorithm Inspired by Classical Dance - Zhang, Jincheng; Zhang, Jindong (Control Systems and Optimization Letters, 2025)
This paper proposes a metaheuristic optimization algorithm based on classical dance, namely the Classical Dance Metaheuristic (CDMH). The algorithm combines the core elements of ballet, Indian classical dance and Chinese classical dance with modern optimization techniques, providing a new approach to high-dimensional optimization problems. The CDMH algorithm optimizes the search process through three stages of simulation: the posture training stage in bllaet, the rhythm and mudra exploration stage in Indian classical dance, and the integration stage of body, rhythm and artistic conception in Chinese classical dance. Experimental results show that CDMH shows good optimization ability in multiple classic optimization problems and can effectively avoid the dilemma of local optimal solutions.